Application of metaphor as a stylistic feature âof Naser Khosrowâs poetryâ - حمید رضایی; ابراهیم ظاهری (مطالعات زبانی و بلاغی)
The aim of this article is to review the material, âstructure, features of metaphor and tropology techniques as âthe most important element of imagination in Naser âKhowsroâs poems. Human organs, various classes of people, ânature, the world and sky are the most important elements âwhich Naser Khowsroâs uses as metaphors in his poems.â Naser Khowsro resorts to imaginary elements including âmetaphor to describe and explain his various notions and for âthis purpose he has employed abstract stipulated metaphor âwhich is easier to comprehend, more than other types of âmetaphor.â Naser Khowsro usually first employs an analogy for âtropology and in the following verses, by eliminating the âsimile or adding to it, changes analogy to metaphor another âtechnique is that he firstly expresses a subject in a verse about âa subject, person, thing or a group and in the following verse âexpresses the metaphor in relation to that subject among âmetaphors in Naser Khowsroâs poems, there are metaphors âwhich are used in conundrum, and by the descriptions âpresented by Naser Khowsro about that conundrum,ââ âfinding âthe simile is easy.â